Animal fables after Darwin : literature, speciesism, and metaphor - Danta, Chris (Cambridge : Cambridge University Press, 2018)
The ancient form of the animal fable, in which the characteristics of humans and animals are playfully and educationally intertwined, took on a wholly new meaning after Darwin's theory of evolution changed forever the relationship between humans and animals. In this original study, Chris Danta provides an important and original account of how the fable was adopted and re-adapted by nineteenth- and twentieth-century authors to challenge traditional views of species hierarchy. The rise of the biological sciences in the second half of the nineteenth century provided literary writers such as Robert Louis Stevenson, H. G. Wells, Franz Kafka, Angela Carter and J. M. Coetzee with new material for the fable. By interrogating the form of the fable, and through it the idea of human exceptionalism, writers asked new questions about the place of the human in relation to its biological milieu.
Prologue: uplifting animals; 1. Looking up, looking down: orientations of the human; 2. The grotesque mouth; 3. 'The highest civilisation among ants': Stevenson and the fable; 4. 'An animal among the animals': Wells and the thought of the future; 5. Animal bachelors and animal brides: Kafka, Carter, Garnett; 6. Scapegoats and scapegraces: becoming sacrificial animal in Kafka and Coetzee; Coda: 'Diogenes of the zoo'.
Title from publisher's bibliographic system (viewed on 04 Jul 2018).
Keywords: Animals in literature; Fables -- History and criticism; Human-animal relationships in literature; Darwin, Charles, -- 1809-1882 -- Influence; Literature, Modern -- 19th century -- History and criticism; Literature, Modern -- 20th century -- History and criticism